SPECIFIC FEATURES OF THE DEVELOPMENT OF WRITTEN SPEECH IN STUDENTS WITH DYSLEXIA AND DYSGRAPHIA (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article is devoted to the study of the specific features of the development of written speech in students with dyslexia and dysgraphia. The study analyzed the causes of written speech disorders, their manifestations, and the difficulties of students in the process of reading and writing. It also covers the influence of phonemic perception, sound analysis and synthesis, memory, attention, and articulatory processes on written speech in children with dyslexia and dysgraphia.